PROBLEMATIKA PESERTA DIDIK MTs.NU NGANTANG DALAM IMPLEMENTASI PEMBELAJARAN JARAK JAUH - Ainiatul Mualimah; Moh Eko Nasrulloh; Lutvi Martha Ayunda (Jurnal Tinta, 2021)
The purpose of this article is to identify obstacles in the teaching and learning process carried out online in MTs NU Ngantang, where the teaching and learning process is carried out at home due to the Covid-19 epidemic. An obstacle to the teaching and learning process carried out at home is not only experienced by students, but also by educators and parents alike. There are obstacles for students because some students still do not understand using internet technology including facilities that are not available. There is an obstacle that is troubling parents, namely the increased expense of expenses due to internet quota costs. Constraints for teachers because they have to communicate and coordinate with parents, other teachers, and the principal without face to face